Improving Entrepreneurial Competence in B2B Negotiation and Affiliate Marketing through Batch 3 Entrepreneurship Workshop - Zainuddin, Zulkifli; Saefullah, Aep; Noviar, Ekky; Ramdhan, Muhammad; Gaffar, Ichsan; Ridwan, Muhammad; Mulasih, Siti; Haryono, Haryono; Pagiling, Sarwan; Akmas, Nabila (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2025)
The Batch 3 Entrepreneurship Workshop aims to improve participants' entrepreneurial competencies, especially in mastering B2B negotiation skills and affiliate marketing. This workshop was held on November 30, 2024 at STIE Ganesha by the implementation team from LPPM and Ganesha LabPreneur. The method of activity with a PAR approach that includes interactive material delivery, hands-on simulations, and participatory discussions. There were 150 participants from MSME players and students who brought gadget devices. The results of the activity showed an increase in participants' understanding of the material taught, with most participants able to practice negotiation techniques and digital marketing strategies. The implication of this activity is to encourage the development of resilient entrepreneurs who are adaptive to digital market changes and strategic business collaboration. This activity provides a practical reference for future entrepreneurship training.